EFFECTIVITY OF ENTOMOPATHOGEN Beauveria bassiana (Bals) Vuill. WITH ADDITION OF INSECT GROWTH REGULATOR (IGR) TO CONTROL Riptortus linearis (HEMIPTERA: ALYDIDAE) - V. S Reychel; Toto Himawan; Bambang Tri Raharjo (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
This research aims to find out the effectiveness of entomophatogen B. bassianawith addition of IGR (Insect Growth Regulator) to control R. linearis. Theexperiment was conducted by using Completely Randomized Design andRandomize Complete Block Design, which each treatment was repeated 3 times.The treatment was a combination of IGR and 10% buprofezin with someconcentrations (0.5 ml/l, 0.75 l/ml, 1 ml/l and 1.5 ml/l) an entomopatogen B.bassiana. The observed variable was the percentage of mortality and the mortalityrate. The results showed that the application of B. bassiana with the addition ofbuprofezin unable to increase the effectiveness of B. bassiana in increasing themortality of R. linearis. In this research indicated that mortality of R. linearis byentomophatogen B. bassiana with the addition of buprofezin not more effectivethan mortality caused by B. bassiana.Keywords: Riptortus linearis, IGR, Beauveria bassiana.